Patient Satisfaction with Pharmaceutical Services at a Hospital Outpatient Pharmacy in West Sumatra, Indonesia - Dian Ayu Juwita; Nurul Qalbi Desri; Dita Permatasari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Patient satisfaction stands as a metric for evaluating the quality of pharmaceutical services. The presence of community requests for high-quality pharmaceutical services has driven pharmacy personnel to enhance these services, aiming to establish patient satisfaction. Objective: The objective of this research is to assess the degree of patient satisfaction with pharmaceutical services in the outpatient pharmacy and to explore how this satisfaction is linked to the patients' sociodemographics. Methods: Conducted at Padang Panjang Hospital's Outpatient Pharmacy in West Sumatra, Indonesia, this descriptive research employed a questionnaire administered directly to patients. The method used involves a questionnaire consisting of 20 questions divided into two dimensions: Friendly Explanation (containing 11 questions) and Managing Therapy (containing nine questions). The questionnaire's validity (r > 0.632) and reliability (0.97). Data analysis was performed utilizing the Likert scale. Results: There were a total of respondents in this study (365 patients). Most of them (64.4%) were female, in the pre-elderly age group (45.2%), had completed high school (41.1%), and were housewives (31.8%). In general, the level of patient satisfaction is categorized as satisfied, with an average score of 3.49. Specifically, the "Friendly Explanation" got a score of 3.69, and the "Management of Therapy" got a score of 3.25. The study indicated notable statistical disparities in patient satisfaction levels based on age, education, and occupation (p<0.05), but gender did not have a significant impact (p>0.05). Conclusion: In summation, the study found that patients were satisfied with the pharmaceutical services at Padang Panjang Hospital's Outpatient Pharmacy.